2006
DOI: 10.1002/ca.20366
|View full text |Cite
|
Sign up to set email alerts
|

Bilateral duplicated internal jugular veins: Case study and literature review

Abstract: A rare bilateral duplication of the internal jugular vein (IJV) was discovered during cadaveric dissection. From each jugular foramen, a single IJV descended to the level of the hyoid bone then divided into medial and lateral veins. The medial IJVs traveled in the carotid sheath; the lateral IJVs coursed posterolateral to the sheath across the lateral cervical region (posterior triangle) of the neck. On the right side, medial and lateral IJVs entered the subclavian vein separately. C2-C3 anterior rami and the … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

1
48
1
1

Year Published

2009
2009
2021
2021

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 61 publications
(51 citation statements)
references
References 35 publications
1
48
1
1
Order By: Relevance
“…The main difference between these two clinical conditions is that in duplication, the IJV that comes as a single vessel from the foramen jugulare bifurcates superiorly and communicates with the subclavian vein distally as two distinct Fenestrated IJVs frequently occur with phlebectasia (local fusiform venous dilatation), which appears as a non-pulsatile cervical swelling that enlarges during the Valsalva maneuver. While abnormalities such as aneurysms and arteriovenous malformations accompany arterial fenestrations, they are rare in venous fenestrations (1)(2)(3)(4)(5). Phlebectasia or aneurysm(s) accompanying fenestration was not observed in our case.…”
Section: Discussionmentioning
confidence: 56%
See 1 more Smart Citation
“…The main difference between these two clinical conditions is that in duplication, the IJV that comes as a single vessel from the foramen jugulare bifurcates superiorly and communicates with the subclavian vein distally as two distinct Fenestrated IJVs frequently occur with phlebectasia (local fusiform venous dilatation), which appears as a non-pulsatile cervical swelling that enlarges during the Valsalva maneuver. While abnormalities such as aneurysms and arteriovenous malformations accompany arterial fenestrations, they are rare in venous fenestrations (1)(2)(3)(4)(5). Phlebectasia or aneurysm(s) accompanying fenestration was not observed in our case.…”
Section: Discussionmentioning
confidence: 56%
“…It proceeds in the carotid sheath together with the common carotid artery before combining with the subclavian vein on the sternal side of the clavicle. The IJV is a significant landmark that is encountered during dissection of the cervical lymph nodes in oncological surgery, central venous catheter insertion, and interventional radiological procedures; familiarity with the probable anatomical variations of the IJV and those of its neighbouring structures is important (1)(2)(3). In this report, a male patient, in whom quite a large extraordinary fenestration was detected in the left IJV during multidetector computed tomography (MDCT), is presented in the light of MDCT findings and the literature.…”
mentioning
confidence: 99%
“…The anatomical course of the jugular veins is usually very consistent; however, anomalies do occur, which may present as a neck swelling or be an subclinical finding [2,3]. Downie et al [4] previous reports of IJV anomalies have used the terms 'duplicated' and 'fenestrated' interchangeably. The main difference between these two conditions is that duplicated IJVs comprise two separate branches along the whole length of the normal pathway, whereas in fenestrated IJVs the two branches reunite before draining into the subclavian veins.…”
Section: Discussionmentioning
confidence: 99%
“…Divisions (fenestrations or duplications) of the IJV are estimated to occur in as much as 0.4% of the population (Prades et al, 2002). In order to avoid confusion between the terms duplication and fenestration, which are used interchangeably in the literature available, Downie et al, (2007) suggested that the term duplication be limited to those cases in which the branches of the anomalous vessel remain separate over the entire course, whereas the term fenestration should be used for those cases in which the branched vessel reunites into a single normal vessel.…”
Section: Discussionmentioning
confidence: 99%